Bioconjugated Manganese Dioxide Nanoparticles Enhance Chemotherapy Response by Priming Tumor-Associated Macrophages toward M1-like Phenotype and Attenuating Tumor Hypoxia - Song, Manli; Liu, Ting; Shi, Changrong; Zhang, Xiangzhong; Chen, Xiaoyuan (ACS nano, 2016)
Hypoxia promotes not only the invasiveness of tumor cells, but also chemoresistance in cancer. Tumor associated macrophages (TAMs) residing at the site of hypoxic region of tumors have been known to cooperate with tumor cells, and promote proliferation and chemoresistance. Therefore, there is an urgent need for new strategies to alleviate tumor hypoxia and enhance chemotherapy response in solid tumors. Herein, we have taken advantage of high accumulation of TAMs in hypoxic regions of tumor and high reactivity of manganese dioxide nanoparticles (MnO2 NPs) toward hydrogen peroxide (H2O2) for the simultaneous production of O2 and regulation of pH to effectively alleviate tumor hypoxia by targeted delivery of MnO2 NPs to the hypoxic area. Furthermore, we also utilized the ability of hyaluronic acid (HA) modification in reprogramming anti-inflammatory, pro-tumoral M2 TAMs to pro-inflammatory, antitumor M1 macrophages to further enhance the ability of MnO2 NPs to lessen tumor hypoxia and modulate chemoresistance. The HA-coated, mannan-conjugated MnO2 particle (Man-HA-MnO2) treatment significantly increased tumor oxygenation and down-regulated hypoxia-inducible factor-1 α (HIF-1α) and vascular endothelial growth factor (VEGF) in the tumor. Combination treatment of the tumors with Man-HA-MnO2 NPs and doxorubicin significantly increased apparent diffusion coefficient (ADC) values of breast tumor, inhibited tumor growth and tumor cell proliferation as compared with chemotherapy alone. In addition, the reaction of Man-HA-MnO2 NPs toward endogenous H2O2 highly enhanced T 1- and T 2-MRI performance for tumor imaging and detection.